2020
DOI: 10.1055/s-0040-1713941
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches to the Orbit: A Neurosurgical Perspective

Abstract: Orbital pathologies can be complex to manage surgically. In this article, we describe some of the most common and relevant approaches to orbital tumours. For each approach we describe the appropriate indications, surgical technique, potential complications, and illustrate a case example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…A critical consequence of reduced neurosurgeon involvement in certain specialty areas is the potential detrimental effect on patient care. In multidisciplinary team settings focusing on these subspecialties, the input of experienced neurosurgeons is indispensable ( Abussuud et al, 2020 ; Peck et al, 2020 ; Rasulić, 2017 ; Robinson et al, 2022 ; Staudt, 2022 ; Zoia et al, 2023 ). Neurosurgical solutions or insights are often paramount for optimal treatment, and the absence of neurosurgical participation may lead to missed opportunities for ideal patient care, potentially resulting in suboptimal outcomes and patient dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…A critical consequence of reduced neurosurgeon involvement in certain specialty areas is the potential detrimental effect on patient care. In multidisciplinary team settings focusing on these subspecialties, the input of experienced neurosurgeons is indispensable ( Abussuud et al, 2020 ; Peck et al, 2020 ; Rasulić, 2017 ; Robinson et al, 2022 ; Staudt, 2022 ; Zoia et al, 2023 ). Neurosurgical solutions or insights are often paramount for optimal treatment, and the absence of neurosurgical participation may lead to missed opportunities for ideal patient care, potentially resulting in suboptimal outcomes and patient dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth muscle cells and elastic fibers are sparsely found in the stroma, and the vascular cavity is filled with thrombosis, reflecting the stasis of blood flow [ 2 ]. Symptomatic lesions require surgical intervention, the approach of which is selected depending on the location of the lesions and the surrounding structure, including extraocular muscles, motor and sensory nerves, and the optic nerve [ 2 , 4 ]. The anatomical complexity of the orbit hinders surgical excision [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic lesions require surgical intervention, the approach of which is selected depending on the location of the lesions and the surrounding structure, including extraocular muscles, motor and sensory nerves, and the optic nerve [ 2 , 4 ]. The anatomical complexity of the orbit hinders surgical excision [ 4 ]. As a minimally invasive treatment, intralesional injection of pingyangmycin is a treatment option for lesions that are particularly difficult to resect due to their deep location, such as lesions in the orbital apex [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An apical drillout to reach the cavernous sinus and its respective cranial nerves obviates invasive approaches such as a craniotomy or lateral orbitotomy. 1 , 2 …”
mentioning
confidence: 99%
“…An apical drillout to reach the cavernous sinus and its respective cranial nerves obviates invasive approaches such as a craniotomy or lateral orbitotomy. 1,2 The incidence of perineural invasion in periocular SCC is 4.3-14.4%, [3][4][5][6][7] although studies from tertiary centers have reported much higher rates ranging from 23.8% to 36.7%. [8][9][10] While the terms "perineural invasion" (PNI) and "perineural spread" (PNS) are at times used interchangeably, they are 2 separate entities.…”
mentioning
confidence: 99%